A method for identifying negative ion storage sites of solid-state batteries
Patent Information
- Application Number
- CN202611038279.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-13
- Publication Date
- 2026-10-27
AI Technical Summary
目前,利用iDPC-STEM技术对T-Nb2O5中阳离子占位的研究尚不充分,尤其是针对Zn2+电化学插层过程中原子尺度占位演化的系统研究,在公开文献中鲜有提及
(1)本发明首次建立了一套完整的、基于球差校正STEM的原子尺度Zn2+存储位点识别方法。该方法将HAADF-STEM(重元素Nb定位)、iDPC-STEM(轻重元素同时成像和衬度差分分析)、原子分辨率EDS面扫描(Zn元素化学确认)和XRD等物相分析(长程结构验证)四种互补表征技术有机整合,形成了从“宏观物相→原子尺度占位→元素化学确认”的多层级交叉验证表征链条。该方法的每一层表征结果为下一层提供约束条件,有效排除了单一表征手段可能引入的伪影或误判,确保了Zn2+占位识别结果的可靠性。
Smart Images

Figure CN122983111A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of microscopic characterization technology of solid-state battery anodes. It proposes a method for identifying ion storage sites in solid-state battery anodes, which solves the technical problems of insufficient site identification accuracy and inability to quantitatively distinguish effective zinc storage sites. Background Technology
[0002] Orthorhombic niobium pentoxide (T-Nb₂O₅, space group Pbam, cell parameters a≈6.18Å, b≈29.3Å, c≈3.93Å) exhibits a unique layered crystal structure: along the c-axis, high-density 4h atomic layers and low-density 4g atomic layers are alternately stacked, with the 4g layers forming natural two-dimensional interlayer channels. Furthermore, in recent years, multivalent ions (such as Zn) have also shown promising development. 2+ Mg 2+ Ca 2+ Al 3+ Batteries, due to their potential for high volumetric energy density, low cost, and high safety, have become a new research hotspot in the field of electrochemical energy storage. Among them, zinc-ion batteries show promising development prospects due to the high theoretical specific capacity (820 mA h / g), low redox potential (-0.76 V vs. SHE), and excellent water / air stability of the zinc metal anode. However, Zn... 2+ (Ionic radius 0.74 Å, charge +2) and common monovalent alkali metal ions (such as Li) + Na + Zn exhibits significant differences in ionic radius, charge density, and coordination preference, and its storage behavior and occupancy mechanism in the host electrode material lattice cannot be simply explained by existing knowledge of monovalent ions. A deeper understanding of Zn is needed. 2+ The atomic-scale storage sites and occupancy configurations in electrode materials are an indispensable scientific basis for developing high-performance zinc-ion battery electrode materials.
[0003] However, the measures currently being taken have at least the following problems: 1) Current traditional characterization methods have inherent limitations in atomic-scale ion occupancy studies: X-ray diffraction (XRD) can only provide long-range average structural information and cannot distinguish the specific occupancy of a particular ion in a unit cell; Raman spectroscopy and X-ray photoelectron spectroscopy (XPS) are sensitive to local chemical environments, but their spatial resolution is far from sufficient to distinguish differences in ion occupancy on individual atomic columns. Density functional theory (DFT) calculations can predict candidate sites for ion occupancy, but the calculation results depend on the selected functional and parameter settings, and their conclusions are uncertain in the absence of direct experimental verification.
[0004] 2) Advances in aberration-corrected scanning transmission electron microscopy (iDPC-STEM) have brought groundbreaking opportunities for the study of atomic-scale ion occupancy. iDPC-STEM imaging technology uses a four-quadrant segmented detector to precisely measure the minute deflections of the electron beam as it passes through the sample. Currently, research on cation occupancy in T-Nb₂O₅ using iDPC-STEM technology is still insufficient, especially regarding Zn. 2 + Systematic studies on atomic-scale occupancy evolution during electrochemical intercalation are rarely mentioned in published literature. Summary of the Invention
[0005] To address the aforementioned problems, the objective of this invention is to propose a method for identifying ion storage sites in the negative electrode of solid-state batteries. This method utilizes HAADF-STEM and iDPC-STEM atomic imaging techniques, combined with atomic resolution energy dispersive spectroscopy (EDS) surface scanning and X-ray diffraction (XRD) phase analysis, to directly observe and determine Zn at the sub-angstrom scale for the first time. 2+ The specific storage site types, spatial locations, and preferred occupancy order between the 4g layers of the T-Nb2O5 lattice reveal the Zn 2+ The atomic-scale storage mechanism in the layered structure of T-Nb2O5 provides atomic-scale experimental evidence for the design of T-Nb2O5 as an electrode material for zinc ion energy storage devices.
[0006] This was achieved through the following technical solutions: A method for identifying ion storage sites in the negative electrode of a solid-state battery includes the following steps: S1. Sample phase characterization: Orthogonal niobium pentoxide was confirmed by XRD. S2. Mechanical treatment: to reduce the particle size of orthogonal niobium pentoxide samples; S3. Electrode preparation: Disperse the sample evenly with ethanol and spin-coat it onto FTO conductive glass to form a T-Nb2O5@FTO electrode. Store the electrode under normal temperature and pressure conditions. S4, Zn 2+ Embedding process: The electrode prepared in step S3 is placed in a Zn-containing environment. 2+ A dual-electrode system (anode: zinc sheet; cathode: T-Nb2O5@FTO electrode) was used in the electrolyte, employing a constant voltage method (0.1 V vs. Zn). 2+ Electrochemically driven ion intercalation treatment was performed on / Zn to obtain Zn 2+ Embedded T-Nb2O5 sample; S5, Identify Zn 2+ Site: (This refers to sites containing and without Zn) 2+ The samples were transferred to transmission electron microscopes (TEM) to acquire atomic-resolution HAADF-STEM and iDPC-STEM images, respectively. By comparing the images, Zn was identified.2+ site; S6. Atomic-scale energy dispersive spectroscopy (EDS) surface scan verification: In the same or adjacent regions imaged in step S4, atomic-resolution EDS surface scan data are acquired to obtain elemental distribution maps of Nb, O, and Zn.
[0007] Preferably, the conditions for electrochemically driving the embedding of Zn divalent cations into layered oxide nanoparticles are as follows: layered oxide nanoparticles are spin-coated onto conductive glass, the concentration of the divalent cation solution is 0.5 M, the processing temperature is 25-80 °C, and the constant voltage is 0.1 V vs. Zn. 2+ / Zn drive time is 10 minutes.
[0008] Preferably, the particle size range of the layered original T-Nb2O5 nanoparticles prepared in step S2 is 30-200 nm.
[0009] Preferably, the mechanical treatment in step S2 uses a planetary high-energy ball mill with a rotation speed of 450 rpm.
[0010] Preferably, in step S5, the iDPC-STEM image is compared with the (001) plane atomic structure model constructed based on the T-Nb2O5 crystallographic parameter Pbam space group to confirm the correspondence between each contrast peak in the image and a specific atomic column, and a mapping table of contrast peak-atomic column-crystal atom points is established; the mapping table should clearly mark the spatial coordinates of 4g interlayer bridging oxygen sites and non-bridging oxygen sites.
[0011] Preferably, in step S1, X-ray diffraction is used to confirm the characteristic diffraction peaks of the orthorhombic phase T-Nb2O5, confirming that the crystal structure conforms to the 4h / 4g alternating layered structure model, and eliminating the interference of pseudo-hexagonal phase TT-Nb2O5 or monoclinic phase H-Nb2O5; the characteristic diffraction peaks include the (001), (180), and (200) crystal plane diffraction peaks.
[0012] Preferably, in step S5, the HAADF-STEM image of the original T-Nb2O5 nanoparticles is used to clearly show the arrangement pattern of the Nb atomic pillars; the iDPC-STEM image of the original T-Nb2O5 nanoparticles in the same region is used to simultaneously show the positions of the Nb atomic pillars and the O atomic pillars.
[0013] Preferably, pixel-by-pixel differential analysis is performed between the HAADF-STEM image of Zn-T-Nb2O5 and the benchmark HAADF-STEM image of the original T-Nb2O5 nanoparticle sample to extract Zn. 2+ Contrast variation signal caused by embedding.
[0014] Preferably, in step S6, the spatial features of the Zn element distribution map are correlated with the spatial features of the contrast change signal in step S5, and the identified contrast change signal originates from the embedded Zn. 2+ ion.
[0015] Preferably, based on steps S1-S6, the embedded Zn 2+ T-Nb2O5 nanoparticles were used as electrode active materials for solid-state zinc batteries; solid-state battery assembly was completed in an inert atmosphere glove box filled with high-purity argon gas and containing less than 0.1 ppm of water oxygen. The operating temperature of the assembled battery was 25-80℃.
[0016] The beneficial effects of this invention compared to the prior art are: (1) This invention establishes for the first time a complete atomic-scale Zn based on spherical aberration-corrected STEM. 2+ A storage site identification method. This method organically integrates four complementary characterization techniques: HAADF-STEM (heavy element Nb localization), iDPC-STEM (simultaneous imaging and contrast difference analysis of light and heavy elements), atomic resolution EDS surface scanning (Zn elemental chemical confirmation), and phase analysis such as XRD (long-range structure verification). This forms a multi-level cross-validation characterization chain from "macroscopic phase → atomic-scale site occupancy → elemental chemical confirmation." The characterization results at each level provide constraints for the next level, effectively eliminating artifacts or misjudgments that may be introduced by a single characterization method, ensuring the accurate identification of Zn storage sites. 2+ Reliability of occupant identification results.
[0017] (2) This invention is the first to directly observe Zn at the sub-angstrom scale. 2+ The specific storage sites in the T-Nb2O5 lattice provide direct experimental evidence for previous theoretical predictions based solely on DFT calculations. The experiment clearly identified Zn... 2+ Nine specific sites occupying two coordination types in the 4g interlayer of T-Nb₂O₅—seven bridging oxygen coordination sites and two non-bridging oxygen coordination sites within the niobium four-membered ring centered at O₆₄ and O₈₅—were previously only partially predicted theoretically and lacked direct experimental verification. This work provides direct, atomic-scale structural evidence for the energy storage mechanism of T-Nb₂O₅ as a zinc ion host material. Attached Figure Description
[0018] Figure 1 Flowchart of the ion storage site identification method; Figure 2 The X-ray diffraction (XRD) pattern and indexing results of T-Nb2O5 nanoparticles in step S1 of this invention are shown. Figure 3These are HAADF-STEM and iDPC-STEM images of the original T-Nb2O5 nanoparticles along the
[001] zone axis of this invention; Figure 4 For the present invention Zn 2+ Atomic-scale imaging of embedded T-Nb2O5 samples; Figure 5 For the present invention Zn 2+ Atomic-scale EDS surface scan image of a T-Nb2O5 embedded sample. Detailed Implementation
[0019] The technical solutions in the embodiments of the present invention will now be described in detail with reference to the accompanying drawings.
[0020] A method for identifying ion storage sites in the negative electrode of solid-state batteries, such as Figure 1 The diagram shown is a flowchart of an ion storage site identification method, which includes the following steps: S1. Sample Phase Characterization: X-ray diffraction (XRD) was used to characterize the T-Nb2O5 sample to confirm that the sample is a pure orthorhombic phase (space group Pbam). Figure 2 As shown, the characteristic diffraction peaks of the orthorhombic phase T-Nb2O5 (space group Pbam) include diffraction peaks of crystal planes such as (001), (180), and (200), confirming that the crystal structure conforms to the 4h / 4g alternating layered structure model and excluding the interference of other crystal phases (such as pseudo-hexagonal phase TT-Nb2O5 or monoclinic phase H-Nb2O5).
[0021] S2. Mechanical treatment: The sample was mixed with zirconia ball milling beads and then continuously compressed in a planetary high-energy ball mill at 450 rpm to reduce the particle size of the orthogonal niobium pentoxide sample, obtaining pristine T-Nb₂O₅ nanoparticles. The prepared layered pristine T-Nb₂O₅ nanoparticles had a particle size range of 30-200 nm. It is noteworthy that the zirconia ball milling beads and sample mixture can be dispersed with ethanol during the electrode preparation step to separate the ball milling beads and sample, as the high density of the ball milling beads allows them to settle naturally in the dispersion.
[0022] S3. Electrode preparation: Disperse the sample evenly with ethanol and spin-coat it onto FTO conductive glass to form a T-Nb2O5@FTO electrode. Store the electrode under normal temperature and pressure conditions. S4, Zn 2+ Embedding process: The electrode prepared in step S3 is placed in a Zn-containing environment. 2+ A dual-electrode system (anode: zinc sheet; cathode: T-Nb2O5@FTO electrode) was used in the electrolyte, employing a constant voltage method (0.1 V vs. Zn). 2+ Electrochemically driven ion intercalation treatment was performed on / Zn to obtain Zn2+ Embedded T-Nb2O5 sample; S5, Identify Zn 2+ Site: (This refers to sites containing and without Zn) 2+ The samples were transferred to transmission electron microscopes (TEM) to acquire atomic-resolution HAADF-STEM and iDPC-STEM images, respectively. By comparing the images, Zn was identified. 2+ Site.
[0023] like Figure 3 The image shows HAADF-STEM and iDPC-STEM images of the original T-Nb2O5 nanoparticles along the
[001] zone axis, displaying the alternating pattern of six-membered rings of Nb atomic pillars (bright contrast) and the positions of O atomic pillars (medium contrast). The HAADF-STEM image is used to clearly show the arrangement pattern of the Nb atomic pillars. The Nb atomic pillars exhibit a characteristic pattern of alternating six-membered rings along the
[001] projection direction, confirming that the imaging region is the (001) plane atomic structure of T-Nb2O5. The iDPC-STEM image of the same region is used to simultaneously display the positions of Nb and O atomic pillars. In the 4g atomic layer region, the O atomic pillar arrangement density is significantly lower than that in the 4h layer region, forming a recognizable sparse contrast feature, indicating the position and geometry of the interlayer ion storage space. The experimental iDPC-STEM image is compared with the (001) plane atomic structure model constructed based on the crystallographic parameters of T-Nb2O5 (Pbam space group, atomic occupancy coordinates) to confirm the correspondence between each contrast peak in the experimental image and a specific atomic pillar, and to establish a mapping table of contrast peaks-atomic pillars-crystal atom points. The mapping table should clearly indicate the spatial coordinates of the bridging oxygen sites and non-bridging oxygen sites in the 4g layer: the bridging oxygen sites are located in the 4g layer at positions that correspond geometrically to the oxygen atoms in the adjacent 4h layer in a bridge-like manner, and the non-bridging oxygen sites are located in the open void regions of the niobium four-membered ring centered on O64 (Wyckoff position 4g) and O85 (Wyckoff position 4g) in the 4g layer.
[0024] Pixel-by-pixel differential analysis is used to compare the atomic-scale structure image after cation embedding with the baseline structure image without cation embedding at the pixel level, extracting the signal of local atomic arrangement changes caused by cation embedding, and determining the specific position of the cation in the crystal. Pixel-by-pixel differential analysis was performed on the HAADF-STEM image of Zn-T-Nb2O5 and the baseline HAADF-STEM image of the original T-Nb2O5 nanoparticle sample to extract Zn... 2+ The contrast change signal caused by embedding, in which pixel regions with positive contrast increments correspond to newly added atoms (i.e., embedded Zn). 2+ The projection position of ). For example, Figure 4 As shown, this is the Zn of the present invention. 2+Atomic-scale imaging of embedded T-Nb2O5 samples was performed, where (a) is a HAADF-STEM image along the
[001] zone axis, and the Nb atomic pillar arrangement pattern is consistent with that of the original T-Nb2O5. The position coordinates of the signal peaks were compared with the contrast peak-atomic pillar-crystal point mapping table established for the original T-Nb2O5 nanoparticles to determine the Zn 2+ The specific crystal atom type occupied by the ion. If the peak is located in the 4g layer at a position that corresponds geometrically to the oxygen atom in the adjacent 4h layer, it is initially determined to be a bridging oxygen site; if the peak is located in the open void region of the niobium four-membered ring centered on O64 and / or O85 atoms in the 4g layer, it is initially determined to be a non-bridging oxygen site.
[0025] S6. Atomic-scale energy dispersive spectroscopy (EDS) surface scan verification: In the same or adjacent regions imaged in step S4, atomic-resolution EDS surface scan data are acquired to obtain elemental distribution maps of Nb, O, and Zn. For example... Figure 5 As shown, this is the Zn of the present invention. 2+ Atomic-scale EDS surface scan images of the embedded T-Nb2O5 sample. The spatial characteristics of the Zn elemental distribution map are correlated with the spatial characteristics of the contrast change signal in step S5: if the EDS signal of Zn spatially matches the peak position of the signal, then the contrast change signal identified in step S5 is confirmed to indeed originate from the embedded Zn. 2+ Ions, eliminating interference from factors such as electron beam irradiation damage, surface contamination, or imaging artifacts.
[0026] Based on steps S5 and S6, atomic characterization tests were performed on the T-Nb2O5 crystal. Combining experimental spectra and quantitative analysis data, this invention reveals the atomic-level storage mechanism of Zn²⁺ within the crystal. The core technological insights include: (1) The 4g atomic layer in the T-Nb2O5 crystal structure contains two types of atoms that can be absorbed by Zn. 2+ Occupied ion storage sites: bridging oxygen sites and non-bridging oxygen sites. Bridging oxygen sites are located in the 4g layer at coordinate positions that correspond geometrically with oxygen atoms in the adjacent 4h layer in a bridge configuration, and their oxygen coordination environment is dominated by bridging oxygen. Non-bridging oxygen sites are located in the 4g layer in the open void region of the niobium four-membered ring centered on O64 (Wyckoff position 4g) and O85 (Wyckoff position 4g). This region is enclosed by four Nb atom pillars along the
[001] direction, and its spatial size is relatively large (effective inner diameter of about 2.0-2.5 Å), and its oxygen coordination environment is dominated by non-bridging oxygen.
[0027] (2) Zn 2+ The physical reason for Zn preferentially occupying non-bridging oxygen sites lies in 2+ The combined effect of Zn's ionic radius (0.74 Å) and charge density (divalent cation). The smaller ionic radius makes Zn... 2+It can enter the compact space at the center of a niobium quaternary ring (effective inner diameter approximately 2.0-2.5 Å); the high charge density allows Zn 2+ It tends to form strong coordination bonds (ionic polarization) with non-bridged oxygens of O64 and O85 (which have higher negative charge density and coordination flexibility).
[0028] (3) The atomic-scale ion storage site identification method of the multi-level cross-validation characterization chain of macroscopic phase → atomic-scale site occupancy → elemental chemical confirmation has significant promotional value, and can be applied to other guest ions (such as Mg). 2+ Ca 2+ Al 3+ Li + Na + This approach is also suitable for studying atomic-scale storage mechanisms in various layered or tunnel-structured oxide electrode materials (such as V2O5, MoO3, TiO2(B), MnO2, Nb2TiO7, etc.).
[0029] Combining the HAADF-STEM, which is sensitive to heavy elements, with single-frame EDS, which has single-atom chemical recognition capabilities, allows visualization of harmful element interdiffusion between the electrode and electrolyte, and precise measurement of the composition, width, and spatial distribution of the high-resistivity interface phase. Using the iDPC-STEM, which is sensitive to light elements, O, N, and other light elements can be directly observed, thus accurately determining whether unexpected insulating impurities (such as rock salt phase structures) have formed at the interface, and finding the physical root cause of increased interface impedance. In one specific embodiment, the electrochemically intercalated Zn, confirmed through steps S1-S6, was... 2+ T-Nb₂O₅ nanoparticles with atomic-scale storage sites and mechanisms are used as electrode active materials for solid-state zinc batteries. The particle size of the T-Nb₂O₅ nanoparticles ranges from 30-200 nm, preferably 30-100 nm, to shorten the solid-phase ion diffusion path and ensure sufficient exposure of the (001) crystal plane. The active material in the electrode sheet is prepared by mixing it with a conductive additive (selected from at least one of Super P, Ketjen Black, carbon nanotubes, or graphene) and a binder (selected from at least one of PVDF, PEO, PTFE, or CMC / SBR). The electrolyte for the solid-state zinc battery is selected from at least one of PEO-Zn(TFSI)₂ polymer solid-state electrolyte, inorganic ceramic solid-state electrolyte (such as LLZO, LATP), or solid gel electrolyte, and the negative electrode is a Zn metal foil or Zn alloy. The T-Nb₂O₅ electrode material is used in Zn-containing... 2+ Electrochemical pre-intercalation treatment is performed in the liquid electrolyte to allow Zn 2+Pre-occupying 4g interlayer sites in T-Nb2O5 forms a stable ion storage configuration, facilitating subsequent reversible cycling in the solid-state battery. Finally, the solid-state battery is assembled in an inert atmosphere glove box filled with high-purity argon and containing water and oxygen content <0.1ppm. The battery operating temperature is 25-80℃. Standard inert gases for solid-state battery glove boxes are typically high-purity argon (Ar), high-purity nitrogen (N2), and helium (He). However, high-purity argon is chosen here because nitrogen reacts with lithium and zinc under high-temperature / electrochemical conditions to form nitrides, and nitrogen alone is strictly prohibited in solid-state battery assembly. Helium (He) is expensive and is only used in research glove boxes for extremely low dew points and special in-situ electron microscopes; it is rarely used in battery production lines.
[0030] In summary, this invention presents a method for identifying ion storage sites in the negative electrode of solid-state batteries. This method utilizes HAADF-STEM and iDPC-STEM atomic imaging techniques, combined with atomic resolution energy dispersive spectroscopy (EDS) surface scanning and X-ray diffraction (XRD) phase analysis, to construct a multi-level cross-validation characterization chain for atomic-scale ion storage site identification, encompassing macroscopic phase, atomic-scale site occupancy, and elemental chemical confirmation. This method solves the technical challenges of insufficient site identification accuracy and the inability to quantitatively distinguish effective zinc storage sites in existing methods, providing a valuable paradigm for experimental research on guest ion storage mechanisms in electrode materials.
[0031] The above embodiments are merely illustrative of the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solutions based on the technical concept proposed in this invention shall fall within the scope of protection of this invention.
Claims
1. A method for identifying ion storage sites on the negative electrode of a solid-state battery, characterized in that, Includes the following steps: S1. Sample phase characterization: Orthogonal niobium pentoxide was confirmed by X-ray diffraction; S2. Mechanical treatment: to reduce the particle size of orthogonal niobium pentoxide samples; S3. Electrode preparation: Disperse the sample evenly with ethanol and spin-coat it onto FTO conductive glass to form a T-Nb2O5@FTO electrode. Store the electrode under normal temperature and pressure conditions. S4, Zn 2+ Embedding process: The electrode prepared in step S3 is placed in a Zn-containing environment. 2+ A two-electrode system (anode: zinc sheet) is used in the electrolyte; Cathode: T-Nb2O5@FTO electrode) Voltage constant method (0.1 V vs. Zn) 2+ Electrochemically driven ion intercalation treatment was performed on / Zn to obtain Zn 2+ Embedded T-Nb2O5 sample; S5, Identify Zn 2+ Site: (This refers to sites containing and without Zn) 2+ The samples were transferred to transmission electron microscopes (TEM) to acquire atomic-resolution HAADF-STEM and iDPC-STEM images, respectively. By comparing the images, Zn was identified. 2+ site; S6. Atomic-scale energy dispersive spectroscopy (EDS) surface scan verification: In the same or adjacent regions imaged in step S4, atomic-resolution EDS surface scan data are acquired to obtain elemental distribution maps of Nb, O, and Zn.
2. The method for identifying ion storage sites on the negative electrode of a solid-state battery as described in claim 1, characterized in that, The conditions for electrochemically driven embedding of Zn divalent cations into layered oxide nanoparticles were as follows: layered oxide nanoparticles were spin-coated onto conductive glass, the concentration of the divalent cation solution was 0.5 M, the processing temperature was 25-80 °C, and a constant voltage of 0.1 V vs. Zn. 2+ / Zn drive time is 10 minutes.
3. The method for identifying ion storage sites on the negative electrode of a solid-state battery as described in claim 1, characterized in that, The particle size range of the layered original T-Nb2O5 nanoparticles prepared in step S2 is 30-200 nm.
4. The method for identifying ion storage sites on the negative electrode of a solid-state battery as described in claim 1, characterized in that, In step S2, the mechanical treatment uses a planetary high-energy ball mill with a rotation speed of 450 rpm.
5. The method for identifying ion storage sites on the negative electrode of a solid-state battery as described in claim 1, characterized in that, In step S5, the iDPC-STEM image is compared with the (001) plane atomic structure model constructed based on the Pbam space group of T-Nb2O5 crystallographic parameters. The correspondence between each contrast peak in the image and a specific atomic column is confirmed, and a mapping table of contrast peak-atomic column-crystal atom point is established. The mapping table should clearly indicate the spatial coordinates of bridging oxygen sites and non-bridging oxygen sites in the 4g interlayer.
6. The method for identifying ion storage sites on the negative electrode of a solid-state battery as described in claim 1, characterized in that, In step S1, XRD is used to confirm the characteristic diffraction peaks of the orthorhombic phase T-Nb2O5, confirming that the crystal structure conforms to the 4h / 4g alternating layered structure model, and eliminating the interference of pseudo-hexagonal phase TT-Nb2O5 or monoclinic phase H-Nb2O5; the characteristic diffraction peaks include the (001), (180), and (200) crystal plane diffraction peaks.
7. The method for identifying ion storage sites on the negative electrode of a solid-state battery as described in claim 1, characterized in that, In step S5, the HAADF-STEM image of the original T-Nb2O5 nanoparticles is used to clearly show the arrangement pattern of the Nb atomic pillars; the iDPC-STEM image of the original T-Nb2O5 nanoparticles in the same region is used to simultaneously show the positions of the Nb atomic pillars and the O atomic pillars.
8. The method for identifying ion storage sites on the negative electrode of a solid-state battery as described in claim 5, characterized in that, Pixel-by-pixel differential analysis was performed between the HAADF-STEM image of Zn-T-Nb2O5 and the benchmark HAADF-STEM image of the original T-Nb2O5 nanoparticle sample to extract Zn. 2+ Contrast variation signal caused by embedding.
9. The method for identifying ion storage sites on the negative electrode of a solid-state battery as described in claim 1, characterized in that, In step S6, the spatial features of the Zn element distribution map are correlated with the spatial features of the contrast change signal in step S5. The identified contrast change signal originates from the embedded Zn. 2+ ion.
10. The method for identifying ion storage sites in the negative electrode of a solid-state battery as described in claim 1, characterized in that, Based on steps S1-S6, embed Zn 2+ T-Nb2O5 nanoparticles were used as electrode active materials for solid-state zinc batteries; solid-state battery assembly was completed in an inert atmosphere glove box filled with high-purity argon gas and containing less than 0.1 ppm of water oxygen. The operating temperature of the assembled battery was 25-80℃.